(untitled) - Huynh, Van Hien (Can Tho, 2010)
This book is designed to equip English learners majoring in translation and interpretation with basic translation tecniques at sentence levels from English into Vietnamese and vice versa. The 30-period course introduces 10 chapter on clear-cut purposes to prepare the prospective graduates to work as translators and/or interpreters.
Keywords: Vietnamese language,Translating and interpreting,English language,Dịch và phiên dịch